The effect of forced disability by using rubber belts and kinematic reactions to improve the motor response and electrical activity of the skill of defending the stadium from flying and diving in volleyball - mehdi adel, ai (sports creativity, 2025)
The effect of forced disability by rubber belts and motor reflexes to improve motor response and electrical activity of pitch defense from flying and snorkeling Revitalize the processes of arousal and cessation of nerve processes. Which leads to the improvement of the transmission of nerve surgeries .. This shows the ability of the athlete to change the motor track during the performance of skills, especially in the game of volleyball, which is characterized by the nature of skills and performance of the game law and medical performance of the plan so that the performance is highly ideal because any error leads to loss of points and thus loss The trainers are trained to develop the physical abilities associated with the skill performance and thus increase the effectiveness of the musculoskeletal system by identifying the speed of the nerve connection through the use of forced training which increases the motor reactions during performance through Use a set of exercises designed for this purpose. The volleyball game is characterized by a special character that distinguishes it from other games due to the nature of the modern performance in the game in terms of strength and speed performance. As a result of the amendments to the law of the game, the modern need to prepare a physical integrated. The game of volleyball is characterized by a set of technical skills and the most important of these skills is the defense of the stadium, which is the cornerstone to build attacks and also repel the attacks of competitors and thus win this skill has many important branches such as defense of the stadium with arms from the bottom and used for balls multiplied by force and speed Here the player takes a place inside the stadium to repel it as well as defend the pitch by diving balls falling under the wall of the block in the space and the skill of defending the stadium by one arm or arms, depending on the nature of the place of the ball and track and speed